Runoff-associated nitrogen and phosphorus losses under natural rainfall events in purple soil area: the role of land disturbance and slope length - Ke Liang; Xiaorong He; Binghui He; Xiaomeng Guo; Tianyang Li (Water Supply, 2022)
Land disturbance and slope length play key roles in affecting runoff-associated nitrogen (N) and phosphorus (P) losses in different forms under natural rainfall. Field monitoring was conducted in nine plots located parallel on a 15° purple slope in southwest China. Three slope lengths (20-, 40-, 60-m) combined with measures of artificial disturbance and natural restoration were implemented. The highest N concentration was observed in soft rainfall events across all plots. The highest P concentration was recorded in heavy rainfall events for the artificially disturbed plots and in soft rainfall events for the naturally restored plots. Land disturbance caused orthophosphate concentration to differ in the 20-m plot, and affected N and P loss amounts in different forms. Slope length caused total dissolved phosphorus concentration to differ in naturally restored plots, and also caused the loss amounts of total dissolved nitrogen and orthophosphate to differ in artificially disturbed plots. Natural restoration reduced loss amounts of total nitrogen and total phosphorus by 62.14–79.05% and 79.28–83.43% relative to artificial disturbance, respectively. Concentrations of nitrate-nitrogen, total phosphorus and dissolved phosphorus were closely correlated with rainfall and runoff variables, respectively, in artificially disturbed plots. Our results highlight the dominant role of natural restoration in reducing erosion and nutrient loss in sloping land. HIGHLIGHTS Roles of land disturbance and slope length in N and P losses by runoff are identified.; Land disturbance rarely causes N and P concentrations to differ, but most N and P loss amounts.; Slope length causes TDN and PO4-P loss amounts to differ in disturbed plots rather than natural ones.; Natural restoration reduces N and P loss amounts relative to artificial disturbance.; Decoupling of linkages between N, P concentrations and runoff rate occurs.;